Case Report on Rapunzel syndrome: a large gastric trichobezoar extending to the proximal jejunum in a young adult female - Mijović, Ksenija; Vasin, Dragan; Hasanagić, Sanela; Vukmirović, Jelica; Tomić, Tijana; Tošić, Vasko; Pavlović, Aleksandar; Mašulović, Dragan; Đurić Stefanović, Aleksandra (Frontiers in Medicine, 2025)
A trichobezoar is an intraluminal mass of hair growing continuously with additional ingestion, while Rapunzel syndrome refers to a giant gastric trichobezoar that extends from the stomach into the small intestine. We present a case of Rapunzel syndrome as an uncommon cause of upper gastrointestinal (GI) symptoms in a young adult woman who denied trichotillomania and trichophagia. Preoperative radiological assessment was pivotal in planning a preferable therapeutic approach. The patient underwent laparotomy and prepyloric gastrotomy, resulting in satisfactory postoperative outcomes. Trichobezoars are extremely rare and predominantly affect young women with underlying psychiatric conditions. Although uncommon, they cause severe upper gastrointestinal symptoms and may even lead to various complications. This case report helps in understanding the presentation of gastric trichobezoar and Rapunzel syndrome, including their range of symptoms, radiological appearance, and associated findings, to make an accurate diagnosis and guide an appropriate treatment approach.